Pengaruh Komposisi Media Tanam Terhadap Pertumbuhan Dan Hasil Edamame (Glycine max (L) Merril) Dalam Polybag - Tio Fernandi Patanduk; Dina Rotua Valentina Banjarnahor (Universitas Tidar, 2026)
This study aimed to analyze the effect of different planting media compositions on the growth and yield of edamame (Glycine max (L.) Merrill) cultivated in polybags and to determine the optimal media composition. The research was conducted from January to April 2025 at the Kartini Experimental Garden, Faculty of Agriculture and Business, Satya Wacana Christian University (UKSW), Salatiga, using a Randomized Complete Block Design (RCBD) with seven treatments and four replications. The treatments consisted of soil alone, soil combined with rice husk charcoal, cocopeat, compost, and their combinations. Observed parameters included plant growth, yield components, protein content, and production cost efficiency. The results showed that planting media composition significantly affected the number of leaves, branches, stem diameter, number of pods, pod weight, seed weight, and shoot weight, but had no significant effect on plant height, root weight, 100-seed weight, and protein content. The combination of soil, rice husk charcoal, and compost produced the best results, with the highest pod number and pod weight. This treatment also showed better production cost efficiency compared to cocopeat-based media. Therefore, the combination of soil, rice husk charcoal, and compost is recommended as an optimal planting medium for edamame cultivation in polybags